Xiao Yao San mitigates corticosterone stimulation-induced hippocampal neuronal damage by inhibiting GR phosphorylation and nuclear translocation via FKBP4 involvement - Xuedi Kang; Ting Wang; Haiping Wan; Wenjun Fu; Songjun Lin (BMC Complementary Medicine and Therapies)
Abstract Background Corticosterone stimulation has profound physiological and neurological effects on individuals, necessitating effective interventions to mitigate its impact. Current therapeutic approaches for corticosterone stimulation injury have limitations, including addiction and tolerance issues. In contrast, historical formulations such as Xiao Yao San, a traditional Chinese medicine formula, have shown promise in addressing changes in corticosterone stimulation-related neuroplasticity. This study aimed to explore the potential of Xiao Yao San in modulating the glucocorticoid receptor (GR) signaling pathway and its downstream effects on hippocampal neuroplasticity under corticosterone stimulation conditions. Methods Primary hippocampal neurons were cultured and exposed to corticosterone to establish a corticosterone stimulation model. Cellular viability, apoptosis, and protein expression were assessed via CCK-8 assays, flow cytometry, and immunoblotting, respectively. Interactions between FK506 binding protein 51 (FKBP51), GR, and p-GR were analyzed via coimmunoprecipitation and GST pull-down assays. The influence of FKBP4 on the competitive binding of GR was explored via similar techniques. The functional consequences of gene knockdown and overexpression were evaluated through cellular assays. Results Xiao Yao San attenuated corticosterone-induced reductions in cell viability and apoptosis, counteracting the detrimental effects of corticosterone stimulation. It downregulated FKBP51 expression and suppressed GR phosphorylation and nuclear translocation. Additionally, it hindered the interaction between FKBP51 and GR/p-GR. FKBP4 overexpression rescued hippocampal neuron viability and protected against the GR phosphorylation and nuclear translocation induced by corticosterone. Conclusion Xiao Yao San exhibited promising effects in ameliorating changes in corticosterone stimulation-induced neuroplasticity through the modulation of the GR signaling pathway. By inhibiting FKBP51-mediated GR phosphorylation and nuclear translocation, Xiao Yao San has potential as an alternative therapeutic strategy for corticosterone stimulation-related conditions. Further clinical investigations and mechanistic studies are warranted to validate its therapeutic efficacy and elucidate its mechanisms of action.